2015
DOI: 10.2147/ijnrd.s61718
|View full text |Cite
|
Sign up to set email alerts
|

Ramadan fasting and chronic kidney disease: does estimated glomerular filtration rate change after and before Ramadan? Insights from a mini meta-analysis

Abstract: Ramadan fasting represents one of the five pillars of the Islam creed. Even though patients are exempted from this religious duty, they may be eager to share this particular moment of the year with their family and peers, taking part in the intense spiritual ceremonies and events that characterize this month. However, there are no guidelines or standardized protocols that can help physicians to properly address the issue of patients with chronic kidney disease fasting in Ramadan and correctly advising them. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 15 publications
(33 reference statements)
1
34
0
Order By: Relevance
“…Currently, there are no uniform and accepted guidelines or protocols that can aid clinicians in consulting CKD patients who wish to adhere to the commandment of fasting during Ramadan [20, 21]. The 2 study groups (fasting and non-fasting patients) had similar demographic and clinical characteristics, including age, sex, eGFR, BMI, hemoglobin, serum albumin, percentage of patients with diabetes and hypertension, and severity of the renal failure (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no uniform and accepted guidelines or protocols that can aid clinicians in consulting CKD patients who wish to adhere to the commandment of fasting during Ramadan [20, 21]. The 2 study groups (fasting and non-fasting patients) had similar demographic and clinical characteristics, including age, sex, eGFR, BMI, hemoglobin, serum albumin, percentage of patients with diabetes and hypertension, and severity of the renal failure (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In recent meta‐analysis carried out by Bragazzi that included patients with stable CKD and not yet on dialysis, it was concluded that such patients can safely fast during Ramadan with no significant change occurring in their glomerular filtration rate as a result of fasting …”
Section: Discussionmentioning
confidence: 99%
“…In recent meta-analysis carried out by Bragazzi that included patients with stable CKD and not yet on dialysis, it was concluded that such patients can safely fast during Ramadan with no significant change occurring in their glomerular filtration rate as a result of fasting. 21 Another systemic review by Bragazzi looked into the effect of Ramadan fasting in 140 subjects with CKD including 40 on hemodialysis, 18 on peritoneal dialysis, and the rest not on dialysis yet. The author found no significant ill effects from fasting on these patients.…”
Section: Hemodialysis International 2015; ••:••-••mentioning
confidence: 99%
“…This is especially true among those with chronic kidney disease (CKD), predisposing them to acute tubular injury. Additionally, dehydration is a major precipitating factor for renal stone development [40][41][42] . Antunes et al, 2017 stated that fasting increase the sensitivity of tumor cell lines to cisplatin-induced cells, and also of those cell lines particularly resistant to any pharmacological treatment [43] .…”
Section: Letter To the Editormentioning
confidence: 99%